(untitled) (The Review of Diabetic Studies, 2025)
Epileptic seizures in children are among the most urgent neurological emergencies requiring immediate and well-coordinated pre-hospital intervention. The rapid response of paramedics plays a critical role in minimizing seizure duration, preventing hypoxia and brain injury, and improving survival outcomes. This systematic review examines recent evidence (2010–2025) on the effectiveness of paramedic rapid response in pediatric epilepsy emergencies. Major electronic databases, including PubMed, Scopus, and Web of Science, were searched for studies focusing on pre-hospital management, response time, and clinical outcomes among children with epilepsy. The findings reveal that shorter response intervals—particularly under eight minutes—significantly improve seizure cessation rates, reduce the occurrence of status epilepticus, and lower hospital admission rates. The review also highlights major barriers such as limited pediatric-specific training, inconsistent protocols, and delayed caregiver response. Integrating advanced dispatch technologies, simulation-based training, and family education programs were identified as key strategies to enhance emergency response. This review concludes that strengthening paramedic readiness and optimizing response systems are essential to achieving better outcomes for children experiencing epileptic seizures in pre-hospital settings.